Answer:
let the number be 'x'
now,
so, the number is 6.
hope it helps
stay safe, healthy and happy.
Id take a guess and say line 1 because the rest looks correct
Answer:
101/3 or 33 2/3
Step-by-step explanation:
7 2/15=107/15
9 13/15=138/15
107/15+52/3+138/15
107/15+138/15+52/3
245/15+52/3
245/15+260/15
505/15
simplify,
101/3
Answer:
![(\frac{f}{g})(x)=\frac{1}{3}(x^2+3x+9)](https://tex.z-dn.net/?f=%28%5Cfrac%7Bf%7D%7Bg%7D%29%28x%29%3D%5Cfrac%7B1%7D%7B3%7D%28x%5E2%2B3x%2B9%29)
Step-by-step explanation:
We have been given that
![f(x)=x^3-27,g(x)=3x-9](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E3-27%2Cg%28x%29%3D3x-9)
We can use the formula for difference of cubes to simplify the function f(x)
difference of cubes - ![a^3-b^3=(a-b)(a^2+ab+b^2)](https://tex.z-dn.net/?f=a%5E3-b%5E3%3D%28a-b%29%28a%5E2%2Bab%2Bb%5E2%29)
![f(x)=x^3-27\\\\=x^3-3^3\\\\=(x-3)(x^2+3x+9)](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E3-27%5C%5C%5C%5C%3Dx%5E3-3%5E3%5C%5C%5C%5C%3D%28x-3%29%28x%5E2%2B3x%2B9%29)
And g(x) can be written as
![g(x)=3x-9\\=3(x-3)](https://tex.z-dn.net/?f=g%28x%29%3D3x-9%5C%5C%3D3%28x-3%29)
Thus, we have
![(\frac{f}{g})(x)=\frac{(x-3)(x^2+3x+9)}{3(x-3}](https://tex.z-dn.net/?f=%28%5Cfrac%7Bf%7D%7Bg%7D%29%28x%29%3D%5Cfrac%7B%28x-3%29%28x%5E2%2B3x%2B9%29%7D%7B3%28x-3%7D)
On cancelling the common factors, we get
![(\frac{f}{g})(x)=\frac{1}{3}(x^2+3x+9)](https://tex.z-dn.net/?f=%28%5Cfrac%7Bf%7D%7Bg%7D%29%28x%29%3D%5Cfrac%7B1%7D%7B3%7D%28x%5E2%2B3x%2B9%29)
Answer:
The Student has 72% out of 100%
Step-by-step explanation:
Its the same thing but with fractions